1991
DOI: 10.1007/bf00315337
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of severe neurological abnormalities after vitamin B12 replacement in the Imerslund-Grasbeck syndrome

Abstract: Vitamin B12 malabsorption in the ileum has been postulated as the underlying cause of the Imerslund-Grasbeck syndrome comprising megaloblastic anemia, proteinuria, and multiple neurological abnormalities. A young Saudi child with spasticity, truncal ataxia, cerebral atrophy, megaloblastic anaemia and proteinuria is described. Replacement therapy with parenteral vitamin B12 resulted in the complete resolution of his neurological findings and brain atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Hemoglobin was maintained above 12 g/dl and blood picture reverted back to normal, but proteinuria persisted. On follow‐up, her weight and height were both maintained at 50th centile and she achieved normal milestones, which is consistent with published data 27,28 . Luder et al reported that AMN mutations in IGS may be associated with disturbed vitamin B12 transport into the CNS, which can explain the neurological involvement noted in our case 29 .…”
Section: Discussionsupporting
confidence: 91%
“…Hemoglobin was maintained above 12 g/dl and blood picture reverted back to normal, but proteinuria persisted. On follow‐up, her weight and height were both maintained at 50th centile and she achieved normal milestones, which is consistent with published data 27,28 . Luder et al reported that AMN mutations in IGS may be associated with disturbed vitamin B12 transport into the CNS, which can explain the neurological involvement noted in our case 29 .…”
Section: Discussionsupporting
confidence: 91%
“…This allows us to hypothesize that the ''Mediterranean cluster'' was mainly the result of frequent combinations of consanguineous marriages and high clinical awareness rather than major founder effects. Several publications about the disease have been published from Turkey [Yetgin et al, 1978[Yetgin et al, , 1983Altay et al, 1995;Celep et al, 1996], Israel [Ben Bassat et al, 1969], and some Arab countries [Abdelaal and Ahmed, 1991;Salameh et al, 1991;Ismail et al, 1997], where clinical awareness of the disease is obvious.…”
Section: Discussionmentioning
confidence: 99%
“…A notable cluster occurs in two Scandinavian countries: Norway [Imerslund, 1960] and Finland [Gräsbeck et al, 1960]. Another cluster occurs in the eastern Mediterranean region in Turkey [Altay et al, 1995;Celep et al, 1996], Kuwait [Ismail et al, 1997], Israel [Ben Bassat et al, 1969], and Saudi Arabia [Abdelaal and Ahmed, 1991;Salameh et al, 1991]. Outside of these regions, only scattered cases have been described, e.g., in South Africa [Stones and Ferreira, 1999], Tunisia [Ben Meriem et al, 1993], France [Flechelles et al, 1997], the United States of America [Mackenzie et al, 1972], Taiwan [Lin et al, 1994], and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Patients have decreased levels of serum Vit B12 in the presence of normal levels of intrinsic factor (IF) (Mackenzie et al 1972;Burman et al 1985). Classically, patients present during childhood with pallor, developmental delays and variable neurological symptoms (Campbell et al 1981;Broch et al 1984;Salameh et al 1991;Wulffraat et al 1994;Altay et al 1995;Carmel et al 2003). The therapy consists of periodic parenteral administration of Vit B12 that restores normal metabolism and haematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is also frequent in several Middle Eastern countries, including Turkey, Kuwait, Saudi Arabia and Israel (Ben-Bassat et al 1969;Yetgin et al 1983;Abdelaal and Ahmed 1991;Salameh et al 1991;Altay et al 1995;Celep et al 1996;Ismail et al 1997;Tanner et al 2004). In Tunisia, 24 cases have been diagnosed, but only some have been published (el Bez et al 1992;Ben Meriem et al 1993;Fitouri et al 2001).…”
Section: Introductionmentioning
confidence: 99%